Numerical Study of the Thermally Conductive Finite Thickness Walls Impact on Heat Transfer Regime in a Closed System in Conditions of Radiant Energy Supply; MATEC Web of Conferences; Vol. 37 : Smart Grids 2015 - Nee A. E. Aleksandr Eduardovich (2015, 2015)
Title screen